Incorporation of Fisheries Policy into Regional Blocs?—Lessons from the EU’s Common Fisheries Policy - Li, Shuo (Fishes, 2022)
As globalization is facing increasing challenges, regionalization demonstrates the potential to effectively address many transboundary issues. Current international fisheries management has attracted criticisms, among which the poor incentives for countries to attend and comply with the rules are notable. This paper aims to explore whether the incorporation of fisheries policies into regional economic blocs can be a solution to improve cross-border fisheries management. The development, problems, and future of the Common Fisheries Policy (CFP) of the European Union are explored in detail. This paper concludes that the evolution and implementation of the CFP provide some precious lessons for the world. An appropriately designed regional fisheries scheme would help to create incentives for countries to participate in regional regimes and improve their fisheries management. Economic incentives, a good institutional design, and financial and scientific support are critical factors in favor of adopting common fisheries policies under regional economic frameworks.